Analysis of Factor Feeding Patterns For Stunting In Toddlers Aged 24-59 Months - Lahdji, Aisyah; Panjalu, Krishnapatti; Anggraheny, Hema Dewi (University of Muhammadiyah Semarang, 2024)
In 2019, the prevalence of stunting was 3.91 percent. In 2020, the prevalence of stunting was 3.72 percent, and will grow to 3.93% in 2021. The prevalence in February of 2022 is 2.60%. The purpose of this study was to determine the factors of feeding patterns for stunting in toddlers aged 24-59 month at Karanganyar I Public Health Center, Demak Regency. This study uses a cross-sectional, quantitative, analytic observational design. Mothers of children aged 24-59 months make up the research sample using the Total Sampling technique. Collecting data using primary, secondary data, interviews with respondents using questionnaire on the factors of feeding patterns which have been tested for validity and reliability. The logistic regression test and the chi square correlation test can be used to determine the relationship between independent and dependent variables and their risk factors. Most mothers of toddlers with stunting have inappropriate eating habits (type, amount, and schedule). Knowledge, education, profession, income, and technology all have relationship with one another (p value 0.05). Knowledge has the greatest impact on incidence stunting, with a p value of 0.015 OR 11.182; (95% CI 1.613 - 77.529). In the working area of the Karanganyar I Public Health Center, Demak Regency, the majority of mothers with toddlers stunting have knowledge about feeding patterns that still need to be improved. The feeding pattern (type, amount, and schedule) used by the mother to meet her toddler's nutritional demands will be more appropriate the greater the mother's knowledge, educational background, employment status, family income, and technological used.